(untitled) (Olhar de Professor, 2022)
This article seeks to approach Paulo Freire’s liberating pedagogy, in view of his centenary, as a pedagogical using of caring for life, dialogue and love for the world. We question whether Freire’s reflective and critical thinking enables an education based on the life and care of others and the world in “dark times”. Based on a bibliographic and documentary research of the works of Paulo Freire (1996, 2001, 2003, 2006, 2013, 2016, 2018), we present, in the article, a pedagogy that emerges from the reality of and with (oppressed, allowing critical awareness as an explanation of oppression and an education built from love and care. Finally, it is concluded that the Brazilian educator remains present in the struggle for human dignity and his thought feeds hope and universal ethics.Este artículo busca acercarse a la pedagogía liberadora de Paulo Freire, en vista de su centenario, como una praxis pedagógica del cuidado de la vida, el diálogo y el amor al mundo. Nos preguntamos si el pensamiento reflexivo y crítico de Freire posibilita una educación basada en la vida y el cuidado de los demás y del mundo en “tiempos oscuros”. A partir de una investigación bibliográfica y documental de las obras de Paulo Freire (1996, 2001, 2003, 2006, 2013, 2016, 2018), presentamos, en el artículo, una pedagogía que emerge de la realidad de y con los (as) oprimidos (as), permitiendo la conciencia crítica como explicación de la opresión y una educación construida desde el amor y el cuidado. Finalmente, se concluye que el educador brasileño permanece presente en la lucha por la dignidad humana y su pensamiento alimenta la esperanza y la ética universal.